KDM4B facilitates colorectal cancer growth and glucose metabolism by stimulating TRAF6-mediated AKT activation - Li, Haijie (J Exp Clin Cancer Res, 2020)
BACKGROUND: Histone lysine demethylase 4B (KDM4B) has been implicated in various pathological processes and human diseases. Glucose metabolism is the main pattern of energy supply in cells and its dysfunction is closely related to tumorigenesis. Recent study shows that KDM4B protects against obesity and metabolic dysfunction. We realized the significant role of KDM4B in metabolism. However, the role of KDM4B in glucose metabolism remains unclear. Here, we sought to delineate the role and mechanism of KDM4B in glucose metabolism in colorectal cancer (CRC). METHODS: We first analyzed the role of KDM4B in glucose uptake and CRC growth. We then investigated the consequences of KDM4B inhibition on the expression of GLUT1 and AKT signaling, also explored the underlying mechanism. Finally, we detected the mechanism in vivo and assessed the potential correlation between the expression of KDM4B and CRC prognosis. RESULTS: We found that KDM4B promoted glucose uptake and ATP production by regulating the expression of GLUT1 via the AKT signaling pathway. KDM4B could interact with TRAF6 and promote TRAF6-mediated ubiquitination of AKT for AKT activation. Furthermore, we demonstrated that KDM4B was overexpressed in CRC specimens and high level of KDM4B was associated with a poor survival rate in CRC patients. CONCLUSIONS: These findings reveal that KDM4B plays an important role in promoting CRC progression by enhancing glucose metabolism.